PENANGANAN KREDIT PEMILIKAN RUMAH SUBSIDI BERMASALAH PADA BANK SYARIAH DALAM PANDANGAN ISLAM (Studi Bank Tabungan Negara Kantor Cabang Syariah Bogor) - Fatmawati Agustina; Tubagus Rifqy Thantawi; Miftakhul Anwar (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This research is motivated by the increasing demand for housing, but trying to get a house at this time is not an easy thing. The increasingly limited amount of land makes house prices increasingly expensive, especially for people with an average regional minimum wage income. BTN KCS Bogor hereby distributes its funds through subsidized mortgage financing. The amount of funds disbursed by BTN KCS Bogor is relatively high enough that the bank has the risk of non-performing financing. Efforts need to be made to deal with problem financing carried out by BTN KCS Bogor which is different from conventional BTN, namely handling problem financing according to sharia values. This research is qualitative in nature and the data collection method is by conducting interviews at PT BTN-KCS Bogor. The analysis used in this study is a qualitative descriptive analysis. The results show that the handling of problematic financing at BTN KCS Bogor is in accordance with Bank Indonesia and the Financial Services Authority regulations, and Islamic values